Loanwords, Barbarisms and Exotisms in Eastern Armenian (an attempt of differentiation) - KAMALYAN, AREVIK (Bulletin of Yerevan University B: Philology, 2021)
In this article, the author gives a classification of foreign words in the modern Eastern Armenian language. In Armenian linguistics, there is still no clear distinction between ordinary borrowings, exotisms and barbarisms. In particular, exotisms are little studied. The paper attempts to distinguish between foreign-language lexical units, penetrated into Eastern Armenian lately. It is also noted that there is a tendency to translate foreign words, although sometimes these “transfers” can hardly be called equivalents, as many linguistic and extra-linguistic aspects, subtleties of translation are not taken into consideration. The article presents the reasons why many translated words remain in dictionaries, scientific articles and are not generally used.
Keywords: foreign words, loanwords, exotisms, barbarisms, national realia, translation problems, translation of foreign words